IDENTIFIKASI BAKTERI PADA TUBUH LALAT RUMAH (Musca domestica Linn.) DI TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) DAN PASAR - Yunita Panca Putri (Biota, 2018)
ABSTRACT Several species of flies are the most important species in public health problems, especially as a disease transmission vector. One of them is Musca domestica. The role of flies in the spread of disease is as a mechanical vector, by bringing the seeds of disease through the limbs. Therefore it is necessary to understand what bacteria found in the body of M. domestica fly in Sukawinatan landfill, Palembang. This study aimed to find out the type of bacteria in the body of M. domestica in Sukawinatan landfill, Palembang and Jakabaring Main Market. This study was conducted from June to August 2017. The sampling site of home fly (M. domestica) was in Sukawinatan landfill and the Jakabaring main market of Palembang. Meanwhile, the research was conducted in Biology Laboratory, Faculty of Mathematics and Natural Sciences, Universitas PGRI Palembang and Microbiology Laboratory of Department of Biology, FMIPA UNSRI Indralaya. Bacteria found on the body of flies were 6 isolates, 4 bacterial isolates in the fly originating from Sukawinatan landfill and 2 bacterial isolates in the fly from Jakabaring main market. Four (4) bacteria were found in Sukawinatan landfill from Salmonella, Providencia, Escherichia and Vibrio genus. Meanwhile, bacteria found in fly species at Jakabaring main market were 2 bacteria from Salmonella and Proteus genus. Keywords:      Bacteria; House fly (Musca domestica).